A construção de uma sociedade livre, justa e solidária : uma interpretação histórica do art. 3º da CRFB e a ordem econômica brasileira - Lacerda Júnior, José Ventura (2024)
The present study aims to perform a historical interpretation of Article III of the 1988 Brazilian Federal Constitution, focusing on its goal of building a free, fair, and solidarity society. Therefore, this research aimed to investigate the fundamental objectives of the Brazilian Republic and their limitations in reaching such goals, within a historical-constitutional and economic perspective. To achieve this purpose, a bibliographic survey was conducted on the topic, with this research having na exploratory, descriptive nature, employing na indirect and qualitative approach, supported by the dialogical, historical, and hypothetical-deductive methods. Primarily, the objectives of the Federative Republic of Brazil as set forth in the 1988’s Federal Constitution were investigated, analyzing their historical premises, and the Real Plan and the Bolsa Família Program were examined as successful examples of achieving these objectives.Subsequently, the historical formation of Economic Law was analyzed, tracing its development throughout Brazilian Constitutions, examining contemporary Economic Order and its relationship with the fundamental objectives of the Republic, and identifying the State’s appropriation by private interests. With this observation, the genesis of the Brazilian State was examined, including the Old Regime and its adaptation in Brazil, the use of Law as a tool for preserving inequalities, and the appropriation of the State, with reference to the Bahia Court of Appeals and the Rio de Janeiro Court of Appeals. The results indicate that the Brazilian State has built a structure to maintain privileges, facing serious limitations in achieving its objectives, primarily due to its capture by private and corporate interests, which has undermined the provisions of the 1988’s Constitution. It is necessary for the State to reclaim its role as a driver and guide of development in order to achieve the objectives outlined in Article III of the 1988 Federal Constitution of the Federative Republic of Brazil.